Following the Footsteps of the Dead. Daša Drndić’s Photo-texts - Giergiel, Sabina (Balcanica Posnaniensia. Acta et studia, 2019)
The starting point for the article is the conviction that in her books, the Croatian author Daša Drndić consistently explores the themes of memory and oblivion about Holocaust and the World War II victims. The paper juxtaposes the excerpts from her two novels: April in Berlin (2009) and EEG (2016). In both of them, the author inserts peculiar photo-texts in which the visual layer mingles with the linguistic one. In the first one, this relation is obvious (photographs and text are set together here), whereas in the second one it is more ambiguous. However, I endeavor to demonstrate that using language, Drndić manages to create the unusual graphic “pictures in motion” that simultaneously envision the contemporary Zagreb as well as the same city from the 1940s. The interpretation of such fragments is additionally enhanced with the considerations on the Croatian capital city’s space which is filled with multiple signs of “difficult heritage” (Sharon Macdonald’s term).